Migrant Longing : Letter Writing across the U.S.-Mexico Borderlands - Chávez-García, Miroslava, 1968- (Book collections on Project MUSE., 2018)
"Drawing upon a personal collection of more than 300 letters exchanged between her parents and other family members across the U.S.-Mexico border, Miroslava Chávez-García recreates and gives meaning to the hope, fear, and longing migrants experienced in their everyday lives both "here" and "there" ("aquí y allá"). As private sources of communication hidden from public consumption and historical research, the letters provide a rare glimpse into the deeply emotional, personal, and social lives of ordinary Mexican men and women as recorded in their immediate, firsthand accounts. Chávez-García demonstrates not only how migrants struggled to maintain their sense of humanity in "El Norte" but also how those remaining at home made sense of their changing identities in response to the loss of loved ones who sometimes left for weeks, months, or years at a time, or simply never returned"--